Addressing Indonesian Child Marriage: Comparative Study of Global Standards and Best Practices - Situmeang, Ampuan; Silviani, Ninne Zahara; Fitri, Winda (Legal Spirit, 2023)
Child marriage is a significant human rights issue as it deprives children around the world of their childhood, education, and safety. Its unfortunately a practice that still has prevalence in Indonesian society. This research is done for the purpose of analyzing the threat of child marriage and the urgency for a dedicated effort to tackle this issue normatively. Through the normative legal research method and supported by comparative analysis, this research analyzes how the Indonesian legal framework fare up to international human rights standards and best practices around the world, in tackling the practice of child marriage. Findings of this research suggest that child marriage can still be considered a neglected human rights abuse, due the minimum number of legal developments throughout the years. The findings expose the legal loophole and the lack of criminalization which can contribute to the prevalence of this dangerous phenomenon. This research serves the purpose of the betterment of human rights protection in Indonesia, specifically on vulnerable underage girls, by providing insights and recommendations that the government may consider for future legal development.